2014
DOI: 10.1007/s12539-014-0190-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and mutational assessment of podocin — A novel drug target to nephrotic syndrome — An in silico approach

Abstract: Non-synonymous single nucleotide changes (nSNC) are coding variants that introduce amino acid changes in their corresponding proteins. They can affect protein function; they are believed to have the largest impact on human health compared with SNCs in other regions of the genome. Such a sequence alteration directly affects their structural stability through conformational changes. Presence of these conformational changes near catalytic site or active site may alter protein function and as a consequence recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The C‐terminus of podocin interacts directly with nephrin to its cytosolic tail domain, where the two proteins oligomerize in lipid rafts to form the filtration slits. Therefore dysregulation in podocin could cause changes in nephrin, which further damages glomerular slit diaphragm functions . Consistent with previous findings, we also observed a significant increase in urinary podocin mRNA expression levels in preeclampsia rats compared to control, indicating compromised slit diaphragm functions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The C‐terminus of podocin interacts directly with nephrin to its cytosolic tail domain, where the two proteins oligomerize in lipid rafts to form the filtration slits. Therefore dysregulation in podocin could cause changes in nephrin, which further damages glomerular slit diaphragm functions . Consistent with previous findings, we also observed a significant increase in urinary podocin mRNA expression levels in preeclampsia rats compared to control, indicating compromised slit diaphragm functions.…”
Section: Discussionsupporting
confidence: 91%
“…With this notion in mind, we also examined the urinary levels of both nephrin and podocin. Podocin is a protein of the band‐7‐stomatin family members, and has a transmembrane domain constructing a hairpin conformation . The C‐terminus of podocin interacts directly with nephrin to its cytosolic tail domain, where the two proteins oligomerize in lipid rafts to form the filtration slits.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin, a slit diaphragm protein belonging to the immunoglobulin superfamily, is identified as a critical podocyte membrane component, maintaining the barrier function of the glomerular capillary wall [21]. Podocin, a membrane protein of the band-7-stomatin family, is considered to be localized on the membranes of podocyte pedicels, oligomerizes in lipid rafts together with nephrin to form the filtration slits [22]. Recently, it has been revealed that the decreased expression of both nephrin and podocin after podocyte injury, may contribute to the development of proteinuria in MN [23].…”
Section: Discussionmentioning
confidence: 99%
“…Information relating to the age, gender, family history, consanguinity was collected from the total cohort and additional information relating to age at disease onset, histopathology and responsiveness to steroid therapy were collected from the patient group. The criterion to distinguish between SRNS and SSNS; and the histopathological variants are given elsewhere [5].…”
Section: Methodsmentioning
confidence: 99%